Strengthening Financial Governance of Village-Owned Enterprises Sumber Arto Based on Private Entity Financial Accounting Standards - Nurdian Susilowati; Lesa Paranti; Alfa Faridh Suni (Warta Pengabdian Andalas, 2024)
Transparent and accountable reporting of financial information is essential in managing Village-Owned Enterprises (BUMDes). BUMDes Sumber Arto has a capital structure that comes from village funds, community funds, and village assets, so many parties are interested in the transparency of the management of these funds. The lack of competence and capacity of BUMDes directors and administrators in preparing reports causes the financial reports that have been prepared to be rejected by the village government. The accountability and transparency of fund management in BUMDes need to be clarified. This partnership program aims to transfer technology and knowledge regarding understanding accounting and presenting financial reports so that it can provide transparent and accountable information to the village government, management, community, and inspectorates. The approach used is Participatory Rural Appraisal (PRA) in counseling, mentoring, and training. The target community is the director and administrators of BUMDes Sumber Arto, Kenteng Village. The service activities were carried out from July to August 2023. The results of the service activities were that the BUMDes Director and BUMDes administrators could identify each business unit's business activities, strengths, and weaknesses. Furthermore, understanding of the accounting side of accounting began to increase, and the successful determination of the chart of accounts proved this. Furthermore, at the transaction input stage, continuous assistance is still needed so that manual notes can be minimized, and we can switch to a spreadsheet system, which is relatively easy to implement.